The political economy of large-scale food fortification in West Africa: Pathways toward harmonization - Resnick, Danielle (International Food Policy Research Institute, 2025)
For two decades, there have been ongoing efforts at harmonizing large-scale food fortification (LSFF) policies and procedures in West Africa. Despite some notable successes, micronutrient deficiencies in the region remain elevated. To identify which bottlenecks exist towards greater harmonization on LSFF, this study adopted a political economy perspective to consider areas of contention over interests, ideas, and institutions between domestic stakeholders, across countries, and within regional bodies. The study finds that West African governments have made impressive strides with harmonizing their LSFF standards and committing to the importance of fortification as one of several instruments for improving micronutrient deficiencies. Likewise, the donor and technical community have worked closely with the West African Economic and Monetary Union (UEMOA), the Economic Community of West African States (ECOWAS), as well as specialized institutions of ECOWAS, such as the West African Health Organization (WAHO), to advance the LSFF agenda, support the private sector and national fortification alliances, and identify new food vehicles for fortification. At the same time, incoherent trade, tax, and macroeconomic policies in a context of multiple shocks and crises, protectionist impulses aimed at building up domestic agro-industries, lack of financial commitment to LSFF structures in the absence of donor support, and uneven financial contributions to ECOWAS and WAHO remain barriers to progress. Learning from these lessons and considering how to address LSFF from a holistic perspective that accounts for West Africa’s unique demographic, economic, and political characteristics will not only benefit extant harmonization efforts in ECOWAS but also help with broader continental alignment on fortification under the African Union’s 2025-2036 food and nutrition security strategy.